Skeletal muscle hypertrophy adaptations predominate in the early stages of resistance exercise training, matching deuterium oxide-derived measures of muscle protein synthesis and mechanistic target of rapamycin complex 1 signaling - Brook, Matthew S; Wilkinson, Daniel J; Mitchell, William K; Lund, Jonathan N; Szewczyk, Nathaniel J; Greenhaff, Paul L; Smith, Ken; Atherton, Philip J (The FASEB journal, 2015)
Resistance exercise training (RET) is widely used to increase muscle mass in athletes and also aged/cachectic populations. However, the time course and metabolic and molecular control of hypertrophy remain poorly defined. Using newly developed deuterium oxide (D2O)-tracer techniques, we investigated the relationship between long-term muscle protein synthesis (MPS) and hypertrophic responses to RET. A total of 10 men (23 ± 1 yr) undertook 6 wk of unilateral (1-legged) RET [6 × 8 repetitions, 75% 1 repetition maximum (1-RM) 3/wk], rendering 1 leg untrained (UT) and the contralateral, trained (T). After baseline bilateral vastus lateralis (VL) muscle biopsies, subjects consumed 150 ml D2O (70 atom percentage; thereafter 50 ml/wk) with regular body water monitoring in saliva via high-temperature conversion elemental analyzer:isotope ratio mass spectrometer. Further bilateral VL muscle biopsies were taken at 3 and 6 wk to temporally quantify MPS via gas chromatography:pyrolysis:isotope ratio mass spectrometer. Expectedly, only the T leg exhibited marked increases in function [i.e., 1-RM/maximal voluntary contraction (60°)] and VL thickness (peaking at 3 wk). Critically, whereas MPS remained unchanged in the UT leg (e.g., ∼1.35 ± 0.08%/d), the T leg exhibited increased MPS at 0-3 wk (1.6 ± 0.01%/d), but not at 3-6 wk (1.29 ± 0.11%/d); this was reflected by dampened acute mechanistic target of rapamycin complex 1 signaling responses to RET, beyond 3 wk. Therefore, hypertrophic remodeling is most active during the early stages of RET, reflecting longer-term MPS. Moreover, D2O heralds promise for coupling MPS and muscle mass and providing insight into the control of hypertrophy and efficacy of anabolic interventions.